2014
DOI: 10.1007/s13398-014-0200-8
|View full text |Cite
|
Sign up to set email alerts
|

A Kowalski–Słodkowski theorem for 2-local $$^*$$ ∗ -homomorphisms on von Neumann algebras

Abstract: It is established that every (not necessarily linear) 2-local *homomorphism from a von Neumann algebra into a C * -algebra is linear and a * -homomorphism. In the setting of (not necessarily linear) 2-local * -homomorphism from a compact C * -algebra we prove that the same conclusion remains valid. We also prove that every 2-local Jordan *homomorphism from a JBW * -algebra into a JB * -algebra is linear and a Jordan * -homomorphism.1991 Mathematics Subject Classification. Primary 47B49 46L40 (46L57 47B47 47D25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 32 publications
(36 reference statements)
0
27
0
Order By: Relevance
“…The main difficulty in the proof of this result is to show that every such a mapping is linear. It is also remarked at the introduction of [7], that "it would be of great interest to explore if the same conclusion remains true for general C * -algebras". Surprisingly, we can give now a very simple proof of the general result as a consequence of our previous corollary and the results in [27].…”
Section: Weak-2-local Symmetric Mapsmentioning
confidence: 92%
See 2 more Smart Citations
“…The main difficulty in the proof of this result is to show that every such a mapping is linear. It is also remarked at the introduction of [7], that "it would be of great interest to explore if the same conclusion remains true for general C * -algebras". Surprisingly, we can give now a very simple proof of the general result as a consequence of our previous corollary and the results in [27].…”
Section: Weak-2-local Symmetric Mapsmentioning
confidence: 92%
“…The main result in [7] proves that every 2-local * -homomorphism from a von Neumann algebra into a C * -algebra is linear and a * -homomorphism. The main difficulty in the proof of this result is to show that every such a mapping is linear.…”
Section: Weak-2-local Symmetric Mapsmentioning
confidence: 95%
See 1 more Smart Citation
“…For 1 ≤ p < ∞ and p = 2, Al-Halees and Fleming [1] showed that ℓ p is 2-iso-reflexive. In the setting of B(H), C * -algebras and JB * -triples there exists a extensive literature on different classes of (weak-)2-local of maps (see, for example, [2,3,4,10,11,13,14,19,20,23,31,35,39,40] and [43]).…”
Section: Introductionmentioning
confidence: 99%
“…In [6] it was established that every 2-local * -homomorphism from a von Neumann algebra into a C * -algebra is a linear * -homomorphism. These authors also proved that every 2-local Jordan * -homomorphism from a JBW*-algebra into a JB*-algebra is a Jordan *-homomorphism.…”
Section: Introduction and The Main Theoremmentioning
confidence: 99%